Proceedings. 11th IEEE International Workshop on Robot and Human Interactive Communication 2002
DOI: 10.1109/roman.2002.1045655
|View full text |Cite
|
Sign up to set email alerts
|

rob@work: Robot assistant in industrial environments

Abstract: In this contribution we present a robot assistant consisting of a mobile platform and a manipulator to support manual workplaces in production environments. We propose a general definition of robot assistants. Two applications for the robot assistant rob@work are described - the assembly of hydraulic pumps and the assistance of manual gas metal arc welding (GMAW). A description of the hardware and software architecture, the man-machine-interface, the task-planner and the path-planning of the robot assistant is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(80 citation statements)
references
References 2 publications
0
66
0
5
Order By: Relevance
“…The work in [10] provides an assistance system for the automation of the secondary assembly process "testing" with a special focus on completeness and correctness. The work in [11] is a major project for the implementation of a software framework for assembling assistive robots with a similar function as in [12][13][14][15] or as addressed in numerous other projects.…”
Section: Human-robot Interaction In the Industrial Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The work in [10] provides an assistance system for the automation of the secondary assembly process "testing" with a special focus on completeness and correctness. The work in [11] is a major project for the implementation of a software framework for assembling assistive robots with a similar function as in [12][13][14][15] or as addressed in numerous other projects.…”
Section: Human-robot Interaction In the Industrial Environmentmentioning
confidence: 99%
“…The context should be analyzed in the very beginning to know which factors affect the product development, so UCD activities can be better tailored to development phases [13]. To get knowledge of the context, several methods can be applied, e.g., participating in training sessions [23], by means of a contextual inquiry or an ethnographic approach [14].…”
Section: User-centered Development and Evaluationmentioning
confidence: 99%
“…In qualitative analysis for collaboration task identification, the possible collaboration solution for each task is identified based on the comparison of the strength of human operator and robot manipulator with respect to performance requirements. Together with the definitions by Helms et al on four types of human-robot cooperation in industrial environment: independent operation, synchronized cooperation, simultaneous cooperation, and assisted cooperation (Helms et al, 2002), the collaboration tasks are identified and summarized in Table 2 for the first hierarchical level assembly tasks in cable harness assembly. The objective of Task 1, 'Prepare parts kit' (Super-ordinate 1) is to gather and arrange the assembly components into parts kit.…”
Section: Collaboration Analysismentioning
confidence: 99%
“…Some of these tasks require the precision and speed of automation, while others benefit from the dexterity and intelligence of human operators." HumanRobot Collaboration (HRC) brings benefits to industrial applications in terms of speed, efficiency, better quality of the production and better quality of the workplace (ergonomic) [2]. As far as now, robotic automation was seldom applied in small batch productions because of the variety of products and of variable production schedules [3].…”
Section: Introductionmentioning
confidence: 99%